Fast and accurate multi-material model for the prediction of laser welded structural response. Issue 6 (2nd February 2021) - Arif, Waseem; Naceur, Hakim; Miran, Sajjad; Leconte, Nicolas; Markiewicz, Eric
Abstract : Purpose: The purpose of this study is to develop an elasto-plastic multi-material shell model by which finite element analysis of laser welded joints is carried out at the interface of the heat-affected zone and base material. Design/methodology/approach: The multi-material shell model is implemented on the simple cantilever and double cantilever welded plates to examine the efficiency of the developed model. Findings: By reducing the computational time approximately 20 times with the developed model, the results obtained in the form of von Mises stress and equivalent plastic strain are found in good agreement as compared with the reference solid model. Originality/value: The accurate and fast prediction of the stresses and strains in the laser welded joints, and the developed multi-material model is helpful to simulate complex industrial welded structures.